2014
DOI: 10.5057/ijae.13.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smelling Green Tea Rich in Aroma Components on EEG Activity and Memory Task Performance

Abstract: We investigated the memory task performance and the central nervous activity after smelling two kinds of pan-fired Japanese green tea to examine their physical and psychological effects. Twenty eight subjects participated in this study. We used Koushun and Kouju for test samples, which were made by different manufacturing processes. After smelling each odor sample, a memory task and an arithmetic task were used to test mental stress. Electroencephalogram (EEG) was recorded before and after smelling the test sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The power-supply interference was removed with a notch filter at 50Hz. Moreover, signals were bandpass filtered by a 5th-order Butterworth filter [2,30] Hz) in order to remove interferences in frequencies not of interest. Independent component analysis (ICA) was then performed, in particular by employing the SOBI algorithm [37], to remove Independent Components related to ocular and muscular activity.…”
Section: Neurophysiological Data Recordingmentioning
confidence: 99%
See 3 more Smart Citations
“…The power-supply interference was removed with a notch filter at 50Hz. Moreover, signals were bandpass filtered by a 5th-order Butterworth filter [2,30] Hz) in order to remove interferences in frequencies not of interest. Independent component analysis (ICA) was then performed, in particular by employing the SOBI algorithm [37], to remove Independent Components related to ocular and muscular activity.…”
Section: Neurophysiological Data Recordingmentioning
confidence: 99%
“…In fact, thanks to the increasing shared knowledge and recent scientific evidence produced by the neuroscientific community, behavioural neuroscience is experiencing an exponential growth in terms of applied research [13][14][15]. Recently, new terms have been coined, such as Neuroergonomics, Neuromarketing, Neuroaesthetics, and others, to include the new neuroscientific disciplines that aim at investigating neurophysiological correlates of humans' behaviour at work [16][17][18], including driving a car [19][20][21][22][23][24], watching television [25][26][27], having a sensorial experience [28][29][30], and in any other activity of daily life. In the context of applied neurosciences, when physiological signals are acquired in real environments, several factors work against the ease of participant recruitment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Watanabe et al [63] found that impaired higher-order olfactory processing in temporal lobe epilepsy patients may inhibit the effects of the ylang-ylang aroma on the P300. Yoto et al [103] investigated the memory task performance and the central nervous activity after smelling two kinds (Koushun and Kouju) of pan-fired Japanese green tea to examine their physical and psychological effects. The results showed that the odor of Kouju may induce a positive emotion.…”
Section: Effect Of Inhalation Of Fragrance On Eeg Activitymentioning
confidence: 99%